Libertad de expresión de funcionarios públicos en la virtualidad y la facultad de bloquear en redes sociales - Ignacio Velazco, Wilder (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2022)
Public officials today use social networks to broadcast ideas, ex-press opinions, communicate about their activities and interact with citi-zens. However, that virtual interaction can be obstructed when public offi-cials block users or followers on their social networks (Facebook, YouTube, WhatsApp, Facebook Messenger, WeChat, Instagram, TikTok, QQ.). If this happens, the citizen is prevented or limited from knowing the ideas and activity of the public official. Blocking followers serves to protect the intima-cy, integrity and private life of users. Its use may be discretionary for people who do not have public responsibility, however, the scenario varies in the case of public officials. In this context, the objective of this work has been to analyze whether public officials can freely block users. The methodology that is followed consists of a qualitative approach, using the analytical and dogmatic method, with a bibliographical and normative review. The con-clusion is that the official does not have the discretionary power to block their networks, since those who follow the account are interested in knowing the information or opinions that it disseminates, in addition, it is of public interest. In such a context, a public official cannot block users and if he does, it limits rights such as freedom of expression and information of citizens.